2011
DOI: 10.1115/1.4005106
|View full text |Cite
|
Sign up to set email alerts
|

Technical and Economic Performance Analysis of Utilization of Solar Energy in Indoor Swimming Pools, An Application

Abstract: In this study, technical and economic performance analyses are conducted in order to determine the optimum collector surface area for indoor swimming pools. Required heat and economical conditions are taken into consideration while performing these evaluations. A brief summary of solar energy source and heat transfer equations for the Olympic pools are given. An Olympic swimming pool is assumed to be in different cities, and energy losses are calculated. For our sample Olympic pool, convective heat loss obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
6
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
1
6
0
Order By: Relevance
“…The Governing Equations that Relats the Solar Fraction Factor (ƒ) and the Collecting Area (Ac) for Each Type of Solar Collector are given below for each considered month, these are: Comparing the shape of the relationship between the solar fraction factor (ƒ) and the solar collecting area (Ac) shown in figures ( 7) to (10), a great similarity is observed between what was reached in this study and what was reached by Klein [8] (developed a relation of the seasonal average solar fraction with the collector area for heating systems) and by Qussai [9] (developed a relation of the seasonal average solar fraction with the collector area for cooling systems). As this relationship is not a linear relationship between them.…”
Section: Effect Of Collector Surface Area (Ac) On Solar Faction Factor (ƒ)supporting
confidence: 66%
See 1 more Smart Citation
“…The Governing Equations that Relats the Solar Fraction Factor (ƒ) and the Collecting Area (Ac) for Each Type of Solar Collector are given below for each considered month, these are: Comparing the shape of the relationship between the solar fraction factor (ƒ) and the solar collecting area (Ac) shown in figures ( 7) to (10), a great similarity is observed between what was reached in this study and what was reached by Klein [8] (developed a relation of the seasonal average solar fraction with the collector area for heating systems) and by Qussai [9] (developed a relation of the seasonal average solar fraction with the collector area for cooling systems). As this relationship is not a linear relationship between them.…”
Section: Effect Of Collector Surface Area (Ac) On Solar Faction Factor (ƒ)supporting
confidence: 66%
“…The present study was to deal with this concept . Kincay et al [9] designed a model for an Olympic swimming pool with an area of 1800 m2 to test theoretically on the climatic conditions of four cities in Turkey (Antalya, Adana, Istanbul and Ankara). The results showed that: In Antalya, the percentage of the use of solar energy 64% and the rate of reduction of the total annual energy 16.2%.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, thermal and physical properties of suitable materials for swimming pool construction are shown in Table 2 [21].…”
Section: Heating Load Of the Swimming Poolmentioning
confidence: 99%
“…The swimming pool ceiling temperature T SPc can be obtained by Eqs. (19)- (21). Gray body configuration factor f SPc also can be calculated from Eqs.…”
Section: Heating Load Of the Swimming Poolmentioning
confidence: 99%
See 1 more Smart Citation